Avatares del pluralismo : usos y abusos del concepto de diversidad cultural en medios institucionales (2016)
ABSTRACT: This article discusses some of the conceptual and operational problems linked to the discourses and dispositions defined by the pluralistic State of Colombia, whose explicit purpose is to protect cultural diversity. Through a critical analysis of those discourses, this study discovers a logic which is strongly influenced by supranational organizations, and which is based on the assumption that the social groups constituting our cultural diversity must possess clearly identifiable, discrete cultures. Although some progress has been made with regard to racism or the rejection of certain traditional alterities, pluralistic dispositions are not consistent with the social realities of the country, a reason why we have to question its effectiveness to counter new forms of discrimination and exclusion in our societies.